Detrital Zircons Dismember Sibumasu in East Gondwana - Zhang, Xiaoran; Chung, Sun-Lin; Lai, Yu-Ming; Ghani, Azman Abd; Murtadha, Sayed; Lee, Hao-Yang; Hsu, Chun-Chieh (American Geophysical Union, 2018)
Sibumasu is inferred to have developed as a united terrane in East Gondwana, with West Sumatra linked to Cathaysia. New detrital zircon U-Pb and Hf isotopic data from Sumatra, complemented by literature data, challenge the above views. The scarcity of early Neoproterozoic zircons in West Sumatra argues against a direct connection between West Sumatra and Cathaysia. Detrital zircons from East Sumatra exhibit age profiles similar to those of Lhasa, West Burma, and Western Australia, with detritus most probably sourced from Western Australia. By contrast, Sibusima (Sibumasu excluding East Sumatra) shows detrital zircon age patterns resembling those of the South Qiangtang and the Tethyan and High Himalaya terranes, whose detrital materials are most likely derived from northern India. Our observations require disaggregation of Sibumasu and a new configuration of northern East Gondwana in the early Paleozoic, with East Sumatra and West Burma occupying a position outboard the Lhasa terrane along the NW Australian margin and Sibusima situated on the northern Greater Indian margin.